2019
DOI: 10.24895/jig.2019.25-1.889
|View full text |Cite
|
Sign up to set email alerts
|

Studi Perbandingan Konsentrasi Klorofil-a Di Semenanjung Blambangan Kabupaten Banyuwangi Menggunakan Data Citra Satelit Aqua Modis

Abstract: <p>Pemetaan kandungan klorofil-a di pesisir pantai banyak dilakukan dengan tujuan untuk mendapatkan gambaran tingkat kesuburan dari lingkungan perairan yang dimaksud. Tingkat kesuburan yang diharapkan dapat memberikan gambaran populasi dari perikanan tangkap yang dibutuhkan oleh masyarakat pesisir dalam meningkatkan kesejahteraan hidupnya. Penginderaan jauh sebagai salah satu teknologi yang baru telah memberikan banyak manfaat untuk pendeteksian dan pemetaan konsentrasi klorofil-a skala global. Tujuan da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It is found that the cubic polynomial regression model is the best for predicting texture values, water content, total dissolved solids, and total acid with correlation coefficients of 0.92, 0.85, 0.99, and 0.32, respectively. In Zainab et al [9], the relationship between RGB color and chlorophyll-a content was found; it is the best equation in the form of an exponential equation with a correlation coefficient of 0.767. In addition, in other studies [10], [11] studied the relationship between RGB colors for the distribution of solid materials, and the best equation was obtained, i.e., the exponential equation with a correlation coefficient of 0.9336 and 0.9075, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the cubic polynomial regression model is the best for predicting texture values, water content, total dissolved solids, and total acid with correlation coefficients of 0.92, 0.85, 0.99, and 0.32, respectively. In Zainab et al [9], the relationship between RGB color and chlorophyll-a content was found; it is the best equation in the form of an exponential equation with a correlation coefficient of 0.767. In addition, in other studies [10], [11] studied the relationship between RGB colors for the distribution of solid materials, and the best equation was obtained, i.e., the exponential equation with a correlation coefficient of 0.9336 and 0.9075, respectively.…”
Section: Introductionmentioning
confidence: 99%